The feasibility study of household units PV cells for carbon emission reduction in developing countries: A case study of N. Cyprus - Agboola, Philips Olaleye; Egelio?lu, Fuat; Agboola, Mary Oluwatoyin (My University, 2010)
In this paper the feasibility of using photovoltaic cells to reduce electricity generation from fossil fuels in North Cyprus (N. Cyprus) was studied. In this work it is proposed to use photovoltaic systems to power heating and cooling systems (i.e., mainly heat pumps) in household units and it was found that this is economically feasible. It was also discovered that despite the extensive use of solar water heaters in N. Cyprus, the awareness of photovoltaic cells is still very low and few house owners take advantage of its economic and environmental friendliness. It was also observed that PV cells are not widely available in the local market; coupled with the fact that formal awareness of energy friendly electricity means is not well promoted in developing countries. The result of this work shows that about 40 % of yearly electricity consumption in N. Cyprus, which is mainly generated from plants using fuel oil no. 6, can be reduced if all household units use PV systems to heat or cool the house depending on the weather conditions. According to the electricity forecast carried out in this paper it was observed that the annual net electricity consumption is expected to increase by 30.65% in the year 2015. This means that the utility company will need to augment its current facilities to accommodate the increment; by expanding its facilities or opting for energy conservation policies. The latter has proved to be inefficient in this part of the world; the former will increase the use of fossil fuel thereby increasing the CO2 emission. This work also provides economic analysis for PV systems investment for household owners and policies to help increase availability of PV cells in N. Cyprus market. © 2010 by ASME.
ASME 2010 4th International Conference on Energy Sustainability, ES 2010 --
Keywords: Carbon emissions; Electricity generation; Electricity-consumption; Energy conservation policy; Environmental friendliness; Feasibility studies; Heat pumps; Heating and cooling systems; Local markets; Photovoltaic systems; PV system; Utility companies; Weather conditions; Carbon dioxide; Developing countries; Economic analysis; Electric generators; Electric load forecasting; Fossil fuels; Fuel oils; Investments; Photoelectrochemical cells; Photovoltaic cells; Photovoltaic effects; Heating